Modification of the analytic hierarchy process (AHP) method using fuzzy logic: Fuzzy AHP approach as a support to the decision making process concerning engagement of the group for additional hindering - Božanić, Darko; Pamučar, Dragan; Bojanić, Dragan (Serbian Journal of Management, 2015)
This paper presents the modification of the AHP method, which takes into account the degree of suspense of decision maker, that is it allows that decision maker, with a certain degree of conviction (which is usually less than 100%), defines which linguistic expression corresponds to optimality criteria comparison. To determine the criteria weights and alternative values, ​​fuzzy numbers are used since they are very suitable for the expression of vagueness and uncertainty. In this way, after applying the AHP method, we obtained values ​​of criterion functions for each of the examined alternatives, which corresponds to the value determined by the degree of conviction. This provides that for different values ​​of the degree of conviction can be made generation of different sets of criterion functions values. The set model was tested on choosing directions of action of the Group for additional hindering, as a procedure wich is often accompanied by greater or lesser degree of uncertainty of criteria that are necessary in relevant decision making.